Capitol punishment [videorecording (DVD)] - Searcy, Nick; Bugard, Chris
Actor Nick Searcy was at the January 6th rally and provides never before seen footage of the January 6th rally. Searcy interviews Proud Boys president Enrique Tarrio, and others who were arrested in SWAT-style dawn FBI raids for being at the event.